Direct ion-beam deposition of Ag nanoparticles using a solid-state silver ion source. (January 2021) - Zuo, Wenbin; Pelenovich, Vasiliy; Tolstogouzov, Alexander; Zhang, Rui; Zeng, Xiaomei; Abudouwufu, Tushagu; Zhang, Xiangyu; Fu, Dejun
Abstract: Ion beam technology has shown itself worth to be an efficient method to produce nanoparticles embedded in dielectrics for photoelectronic devices. However, direct ion-beam deposition of nanoparticles (NPs) on the surface of dielectrics is rarely reported because the conventional metal ion source runs into difficulties to generate low energy (<10 keV) ion-beams. Herein, Ag NPs are directly deposited on the surface of Si substrates using the recently developed solid electrolyte ion source (SEIS), which possesses advantages of compactness, simple working conditions, and ability of emitting ion-beam at an energy of few keV. The composition, morphology and size of the synthesized Ag NPs are studied. Precise control of the NPs size including in-plane diameter and height is achieved by a modulation of the ion implantation dose. Localized maskless deposition of metal films on semiconductor surface is also expected using the SEIS device. Highlights: A direct ion-beam deposition technology based on solid electrolyte was produced. Spherical Ag NPs was obtained and randomly distributed on the entire Si surface. The Ag NPs size including in-plane diameter and height were modulated by ion dose.